Rehabilitation of patients in the subacute phase of stroke using the ReHand robotic system: a randomized controlled trial - Amirbekova, Mariyam; Kispayeva, Tokzhan; Izbassarova, Akmaral; Adomaviciene, Ausra; Sorokina, Marina; Zhunussova, Tomiris (Frontiers in Human Neuroscience, 2025)
BackgroundUpper limb motor impairment after stroke is a major cause of limitations in daily activities and reduced quality of life. Although traditional rehabilitation is effective, it is often insufficiently intensive and lacks focus on fine motor activation. Portable soft exoskeletons offer a promising approach to intensify recovery. This trial aimed to evaluate the effectiveness of the ReHand robotic system in subacute stroke rehabilitation.MethodsThis Randomized Controlled Trial (RCT) included 120 patients in the subacute period of stroke. Participants were stratified by age and motor deficit severity and randomized into the intervention group (robotic therapy + standard therapy) or control group (standard therapy only). The intervention was delivered 5 times per week over 8 weeks. The primary outcome was change in Fugl-Meyer Assessment for Upper Extremity (FMA-UE); secondary outcomes included Barthel Index (BI), Functional Independence Measure (FIM), National Institutes of Health Stroke Scale (NIHSS), modified Wolf Motor Function Test (mWMFT), Frenchay Arm Test (FAT), Disabilities of the Arm, Shoulder and Hand (DASH), and Hospital Anxiety and Depression Scale (HADS). Statistical analysis was performed in Python (v3.11). Normality was assessed with the Shapiro–Wilk test; the Mann–Whitney test was used for intergroup comparisons; Pearson’s χ2 test with Yates’ correction was used for categorical variables. Effect size was calculated using Cliff’s delta; rank-ANCOVA was performed via the Quade method. Significance was set at p < 0.05.ResultsThe intervention group demonstrated significantly greater improvements in upper limb motor impairment compared to the control group, as reflected by larger gains in FMA-UE scores. Clinically meaningful improvements (≥5.25 points) were observed in 91.7% of patients in the intervention group versus 43.3% in the control group. All secondary outcomes also showed significant improvements in the intervention group (p < 0.001). No adverse events were reported in either group.ConclusionWhen combined with standard therapy, the ReHand robotic system may enhance upper limb recovery after stroke and appears to be a safe and feasible adjunct to multidisciplinary rehabilitation programs.Clinical trial registrationClinicalTrials.gov, identifier (NCT06937346).